1987
DOI: 10.2307/3577085
|View full text |Cite
|
Sign up to set email alerts
|

The Repair of Double-Strand DNA Breaks Correlates with Radiosensitivity of L5178Y-S and L5178Y-R Cells

Abstract: To better understand the basis for the difference in radiosensitivity between the variant murine leukemic lymphoblast cell lines L5178Y-R (resistant) and L5178Y-S (sensitive), the production and repair of DNA damage after X irradiation were measured by the DNA alkaline and neutral elution techniques. The initial yield of single-strand DNA breaks and the rates of their repair were found to be the same in both cell lines by the DNA alkaline elution technique. Using the technique of neutral DNA elution, L5178Y-S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(36 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…The defect in DNA repair in LY-S (sensitive) cells, whicht could be expected from the pronounced susceptibility to tritiated compounds and the lack of a low dose-rate-sparing effect (Beer et al 1985), was demonstrated with pH 9.6 filter elution and premature chromatin condensation (Wlodek and Hittelman 1987). The earlier finding of slower repair of DNA strand breaks [alkaline sedimentation (Korner et al 1977)] was treated with some reservation because of the high (100 Gy) radiation dose applied.…”
Section: Discussionmentioning
confidence: 99%
“…The defect in DNA repair in LY-S (sensitive) cells, whicht could be expected from the pronounced susceptibility to tritiated compounds and the lack of a low dose-rate-sparing effect (Beer et al 1985), was demonstrated with pH 9.6 filter elution and premature chromatin condensation (Wlodek and Hittelman 1987). The earlier finding of slower repair of DNA strand breaks [alkaline sedimentation (Korner et al 1977)] was treated with some reservation because of the high (100 Gy) radiation dose applied.…”
Section: Discussionmentioning
confidence: 99%
“…The high sensitivity of LY-S cells to x-rays (Do=0.5 Gy, Beer et al 1983) is reasonably explained by the impairment of double-strand break (DSB) rejoining (Wlodek and Hittelman 1987). An additional feature of LY-S cells is high initial DNA damage, estimated by neutral elution (Wlodek and Hittelman 1987) or by the fluorescent halo technique (Kapiszewska et al 1992). The radiation-resistant subline LY-R is H202-sensitive (Bouzyk et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The xrs, XR-1 and L5178Y-S mutants have been reported to show defective double-strand break (dsb) rejoining (Kemp et al, 1984;Giaccia et al, 1985;Evans et al, 1987;Wlodek & Hittelman, 1987) measured by neutral filter elution. The irs mutants have no measurable impairment of dsb rejoining, but irsl was found to have low repair fidelity compared with its parent line, V79, using plasmid reconstitution (Debenham et al, 1988b).…”
mentioning
confidence: 99%